Managing of Emotions of Military Students in the Educational Process of the University - Józef LEDZIANOWSKI; Lesław WEŁYCZKO (Communications of International Proceedings, 2020)
The article presents the most important aspects related to the deliberate and rational management of student’s emotions in the didactic process of a military university. The in-depth knowledge of these problems and the well-established competences of academic teachers and commanders of military students subdepartments largely determine how the didactic process will proceed at the university. Whether it will be based on fear and constant emotions, sometimes unjustified, or on mutual cooperation between the teachers and the taught, where emotional intelligence and many of the determinants described in this article will make this didactic process effective and efficient, as a result of which the graduates will have a properly formed personality and acquire the necessary knowledge and skills to be professional commanders (educators and trainers) in military units.
Keywords: Personality; Competence; Leadership; Emotional Intelligence; Management; Emotions; Feelings; Sense of Value; Motivation; Mood.